PARENTING IN THE MILLENNIAL ERA (Analysis of Childcare Models in the Digital Age with Contemporary Islamic Education) - Afandi Afandi; Achmad Anwar Abidin (Attaqwa: Jurnal Ilmu Pendidikan Islam, 2022)
Children are always associated with the parents who give birth to and raise them, because peoplehave the most important role in the child's life in the future.  In the digital era, sources of information are increasingly open and there are almost no restrictions on the information received, including children who are also affected. The digital age has a very positive impact, but it also has a negative impact. In this digital era, parenting or the role of parents is needed to guide and supervise children when they are already addicted to the sophistication of digital technology. It all depends on the parenting of his own parents to keep a child with a disciplined attitude of learning. Differences in parental parenting will have an impact on the child's learning discipline. This research uses the use of qualitative descriptive, and the research method used is a literature study, which is research conducted using several books, journals related to problems and research objectives. Parents play a big role in the development of children, in digital areas parents must accompany and be more careful in parenting patterns by Utilizing Technological Developments In More Organized Parenting, Have a Plan, keep spending time with family and appreciate the child's space. Child Parenting in the Digital Age is divided into three categories, namely: (1) authoritarian parenting; (2) democratic parenting; (3) permissive parenting. All types of parenting have their own advantages and disadvantages. In the analysis from the perspective of contemporary Islamic education, it is found that All parenting patterns in the perspective of Islamic education are directed at how children achieve happiness in the world and the hereafter not only success in their world life but also able to obtain success later in the afterlife whose indicator is to have adequate emotional and spiritual intelligence